Model-Based Systems Engineering for Aircraft Design With Dynamic Landing Constraints Using Object-Process Methodology - Linwen Li; Natali Levi Soskin; Ahmad Jbara; Moti Karpel; Dov Dori (IEEE Access, 2019)
We present a model-based systems engineering (MBSE) framework using object-process methodology (OPM, ISO 19450) for civil transport aircraft design with dynamic landing constraints. The framework integrates the aircraft system development life cycle processes into a holistic MBSE model, incorporating into it the specific aircraft dynamic loads model-based design (MBD) domain. Using this framework, we also perform model-based requirements analysis, validation, and verification. The model parameter set is governed by a unified format used for both the MBSE and MBD domains. The resulting model enables aircraft design processes to start being formalized at the early conceptual design stage and carry on to detailed design, adding value to system lifecycle processes by integrating and streamlining the MBSE and MBD domains into a more holistic framework with seamless transition between these two major stages.